Isolation of Legionella pneumophila from clinical specimens via amoebae, and the interaction of those and other isolates with amoebae. - Rowbotham, T J (1983)
The development of an amoebal enrichment method, for the recovery of viable Legionella pneumophila from clinical materials is described. The method has been used successfully in five of six cases of Legionnaires' disease in which L pneumophila was isolated. Studies on those L pneumophila isolates led to the discovery that virulent legionellae are attracted to, and attack suitable host amoebae, rather than infection following chance ingestion.